(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
As budding nations gradually adopt the use of IT services to store medical records, several healthcare facilities are still unable to exchange information because of limited access to high speed internet service and high cost of operations. Established HIE implementations are designed to rely primarily on such tools as the internet. As a result, healthcare facilities in budding nations cannot embrace HIE to the maximum to accomplish interoperability. A versatile and flexible HIE system was developed in this research to accomplish exchange of health information. The system adapted the technique for direct exchange of HIE. This technique uses the Unstructured Supplementary Service Data (USSD) as the medium for transmitting encrypted HL7 version 2.X encoded messages adopting the Signaling System 7 (SS7) exchange protocol. The system was tested by establishing and studying a normal situation of communication between two health facilities that were interacting. The information recorded included the quality of the message delivery, the length of the communication and the precision of the contents of the transmitted message. In conclusion, the findings indicate a process that relays health information of patients in Internet-deprived regions in an effective and safe way. This idea of transmitting encrypted cryptic messages through USSD can also be applied to several other fields of study, where the sharing of information is restricted by poor Internet service availability.